Sustainable forest management based on state practice in Central Africa countries - Assembe-Mvondo, Samuel; Eba'a Atyi, R.; Lescuyer, G.; Wardell, A. (2011)
This piece of writing briefly reviews the nterpretation of the concept of sustainable forest management (SFM) deduced from state ractice in some Central Africa countries. This assessment of SFM practices draws upon the earlier and highly variable definitions of sustainable development. It demonstrates that some progress has been made in terms of the more nuanced meanings of SFM now adopted by States in Central Africa. This reflects the fact that it is difficult to find a good balance between the three functions (economic, social and environmental) which structure the concept of SFM. Congo Basin countries seek to translate SFM by institutionalizing and implementing forest concessions, protected areas and community forestry. However, these efforts have been hindered by some governance shortcomings.